Determinants of land degradation in Jammu and Kashmir: implications for land governance - S H Baba; M H Wani; B A Zargar; Ishrat F Bhat (Agricultural Economics Research Review, 2023)
To arrive at good land governance imperatives, we study land degradation in Jammu & Kashmir. The panel regression estimates indicate that rural literacy and direct institutional credit to farmers reduce land degradation in the state and rural population density and urban population growth increase it. Public investment in agricultural production is critical for land development, irrigation, and forestry, but it has declined recently in absolute and proportionate terms, and poor execution of acts and reforms have brought about deficits in land governance. The study suggests options for making the state’s land governance policy efficient and developing its resources.